2019
DOI: 10.1186/s12978-019-0691-z
|View full text |Cite
|
Sign up to set email alerts
|

Syphilis and human immunodeficiency virus infections among pregnant women attending antenatal care clinic of Gondar family guidance association, Northwest Ethiopia: implication for prevention of mother to child transmission

Abstract: Background Sexually transmitted infections constitute a major public health problem worldwide. Syphilis and HIV infections cause various adverse pregnancy outcomes. Therefore, the aim of this study was to determine the seroprevalence of HIV and syphilis infections among pregnant women at Gondar Family Guidance Association clinic, northwest Ethiopia. Methods A retrospective study was conducted using sociodemographic and laboratory data obtained from registration books of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
18
2
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 32 publications
4
18
2
4
Order By: Relevance
“…Also our finding are in accordance with previous study conducted in Democratic Republic of Congo where HIV infection rate was estimated to be 3.6% [12]. Furthermore, the observed HIV prevalence of 4.2% and syphilis of 1.2% in this study are consistent with the study conducted at Gondar, Ethiopia 4.1% and 1.9% respectively [13]. However, HIV prevalence observed in this study is a bit higher compared to the national prevalence of HIV (3%) in general population and the prevalence of Syphilis was also a bit high compared to 1.4% found in pregnant women at national level in Rwanda [14,15].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Also our finding are in accordance with previous study conducted in Democratic Republic of Congo where HIV infection rate was estimated to be 3.6% [12]. Furthermore, the observed HIV prevalence of 4.2% and syphilis of 1.2% in this study are consistent with the study conducted at Gondar, Ethiopia 4.1% and 1.9% respectively [13]. However, HIV prevalence observed in this study is a bit higher compared to the national prevalence of HIV (3%) in general population and the prevalence of Syphilis was also a bit high compared to 1.4% found in pregnant women at national level in Rwanda [14,15].…”
Section: Discussionsupporting
confidence: 92%
“…Also, it is in accordance with Roch Fabien Niama et al, where in their finding, age group above 25 year of age had increased risk of infection than others [12]. This may be attributed to the increased risk of exposure to STIs, since this age group is very sexually active [13] In this study, a bigger proportion of HIV and syphilis positivity were seen in cohabitant women compared to the married women. This is similar to the previous studies suggesting them to be a high risk group compared to the married women or general population [12,18,19].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…[11][12][13] Another study conducted from Gondar Family Guidance Association had shown that 1.9% of the pregnant women were positive for syphilis. 14 Syphilis clinical manifestations are classified into multiple stages as primary, secondary, latent (early and late) and tertiary syphilis. 9 Primary syphilis facilitates the transmission of HIV infection and it can contribute to the spread of HIV infection.…”
Section: Introductionmentioning
confidence: 99%